2016
DOI: 10.1371/journal.pone.0163224
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use During Hospitalization: Automated Identification of Potential Medication Errors and Systematic Assessment of Preventable Adverse Events

Abstract: ObjectiveBenzodiazepines and “Z-drug” GABA-receptor modulators (BDZ) are among the most frequently used drugs in hospitals. Adverse drug events (ADE) associated with BDZ can be the result of preventable medication errors (ME) related to dosing, drug interactions and comorbidities. The present study evaluated inpatient use of BDZ and related ME and ADE.MethodsWe conducted an observational study within a pharmacoepidemiological database derived from the clinical information system of a tertiary care hospital. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(45 reference statements)
1
4
0
1
Order By: Relevance
“…With 10.3389/fpsyt.2022.959399 regards to mood stabilizers, the increase in prescription could reflect a change in their use for analgesic purposes as gradually emerged in medical literature (76)(77)(78). Overall, these findings mirror the aforementioned change in antidepressants prescription in the last decades, the increased prevalence of bipolar disorders and confirm the frequent use of benzodiazepines in medical settings both for sleep control as well as a means for rapid tranquillization (79). These data underline the need to further train non-specialists in psychiatry, within and outside the hospital, about the risks of benzodiazepines use in medically ill patients, especially in the elderly (80, 81), as well as the need to further develop CLP services with general practitioners to monitor pharmacotherapy (82).…”
Section: Discussionsupporting
confidence: 69%
“…With 10.3389/fpsyt.2022.959399 regards to mood stabilizers, the increase in prescription could reflect a change in their use for analgesic purposes as gradually emerged in medical literature (76)(77)(78). Overall, these findings mirror the aforementioned change in antidepressants prescription in the last decades, the increased prevalence of bipolar disorders and confirm the frequent use of benzodiazepines in medical settings both for sleep control as well as a means for rapid tranquillization (79). These data underline the need to further train non-specialists in psychiatry, within and outside the hospital, about the risks of benzodiazepines use in medically ill patients, especially in the elderly (80, 81), as well as the need to further develop CLP services with general practitioners to monitor pharmacotherapy (82).…”
Section: Discussionsupporting
confidence: 69%
“…16 Os benzodiazepínicos são prescritos principalmente para o tratamento de insônia e ansiedade, podendo afetar a função cognitiva. Seu efeito sedativo é um fator de risco para quedas e fraturas 16,21,17 . O aumento no risco de quedas e fraturas entre idosos usuários de benzodiazepínicos tem sido atribuído a duas propriedades desses medicamentos: atividade sedativa e bloqueio α-adrenérgico.…”
Section: Discussionunclassified
“…In this study, no adverse event was observed in all the patients. A large observational study of 53,081 patients in an European country revealed that GABA A receptor hypnotic agents (eg, lorazepam and zolpidem) were administered to 48.3% of hospitalized patients 6. In consideration of the potential side effects of hypnotic agents, GABA A receptor hypnotic agents might 1) modify sleep architecture, 2) increase respiratory events during sleep (cause respiratory depression), 3) increase the risk of falls (or bone fracture), and 4) cause acute cognitive dysfunction and hallucination 15,16,27,29,30.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines and/or non-benzodiazepines (ie, type A gamma-aminobutyric acid [GABA A ] receptor hypnotic agents) are most frequently used to treat insomnia worldwide, even during hospitalization 6. However, there are several concerns about the routine use of GABA A receptor agonists for patients with insomnia who might have undiagnosed OSA.…”
Section: Introductionmentioning
confidence: 99%